Psychosocial foundations for healthy and successful marriage and family life (2012)
The human family has been recognized since antiquity as the most primary and fundamental unit of society and the bulwark of health and happiness of the human person. It has been variously referred to as the primary social support unit or system for any human person, the primary unit of socialization and the primary cell of human existence and society. For these reasons, all human cultures and societies had valued it, accorded rights and privileges to it and considered higher levels of society as only subsidiary to it in all of the above-named functions. Family indeed is the centre of our life and productivity. Therefore, the nature of the human family as our first and best love, our first and best home, our first and best school, our first and best faith community, our first and best bank, our first and best court of justice and equity, and our primary and best unit of socialization are explored in this article. Similarly, the need that such marriages that will produce such families have for the some very essential psycho-social foundations are explored; namely, for them to be permanent/covenantal unions, to be based on common core values of the spouses, to be monogamous as well as extended on both sides of the originating families of the couple.